The effect of levels of nitrogen fertilization and cutting height on the growth characteristics and yield of green and dry forage of white corn (Sorghum bicolor L.) (Texas Journal of Agriculture and Biological Sciences, 2023)
A field experiment was conducted in the field of the College of agriculture, University of Basrah،lkarma Location (30.57 north latitude and 47.80 west longitude). The field experiment Carried out in spring agricultural Season (2021_2022). The aim of the study was to estimate the effects of five different levels of nitrogen fertilizer (0,150, 200, 250, 300) kg N ha-1 in Silt loam Soils and at three different levels of cutting heights (10,20,30) cm on the growth and Forage yield of Sorghum bicolor L. which was planted on 1/4/2022. The experiment was applied, according to factorial experiments using randomized Complete block (R.C.B.D) with three replications. The replications were distributed randomly in each section. Three plant cuts were taken from the harvest. The following three traits were studied: Plant height, number of tillers, and Forage yield. The results showed 250 kg N ha-1 has excelled, recording the highest average of plant height (168.70, 136.13, 112.97) cm, and the highest average for the number of tillers ( 4.10, 2.79, 2.36) tiller plant-1 , and also has achieved the highest average for green Forage yield (39.35, 33.91, 22.83) t ha-1 , and for dry Forage yield (10.21, 9.73, 6.44) t ha-1For the first, Second, third plant cuts respectively. The results have also shown that cutting height effects were significant in Most of the following traits: growth, food yield, genotype of different plant cuts. The cutting height of (10 cm) has achieved the highest average for the number of tillers (3.46, 2.13 , 2.06) tiller plant-1 , and the highest green Forage Yield ( 32. 20, 27. 26, 18. 71) t ha-1 , and for dry Forage yield ( 8. 11, 7.74, 5.07) t ha-1 that for the first, Second and third plant cuts respectively. The effects of interaction between nitrogen fertilizers and cutting heights were significant in most traits of growth, dry and green Forage yield which recorded coefficient of interference equals(250 kg N ha-1 ) with cutting height of (10 cm) , The highest average for the number of tillers (4.27, 3.05, 2.65) tiller plant-1 , and the highest average for green Forage yield (43.47, 39.07, 25.87) t ha-1 , and for dry Forage yield (11.25, 11.30, 7.16) t ha-1 For the first, second, and third plant cuts respectively.